Development of interactive teaching materials based on inquiry based learning models based on the outcome-based education curriculum in analytical chemistry learning - Anna Juniar; Siti Rahmah; Tua Paimaon Tambunan; Pravil M Tambunan (Pascasarjana Universitas Negeri Medan, 2023)
This research to develop an IBL-based electronic e-module integrated with the OBE curriculum in analytical chemistry learning. This research is a development research using the ADDIE model which consists of 5 stages: Analysis. Design, Development, Implementation and Evaluation. The sampling technique uses purposive sampling as many as 28 preservice chemistry teachers. Research data were obtained from a validation questionnaire for media experts, material experts, linguists and student responses to the developed e-module with BSNP criteria. Material expert validation obtained an average content feasibility of 3.22, language eligibility 3.52 and presentation feasibility 3.73 IT expert validation obtained an average for design indicators 3.75, display 3.75 and visual 3.3 and usage 3.75. Student response to learning using an electronic IBL-based e-module integrated with the OBE curriculum for display is 89.99%, content quality is 92.85%, usage is 93.3% and usefulness is 93.15%. Implementation of interactive e-module products based on inquiry based learning in learning that can improve student chemistry learning outcomes in the Analytical Chemistry course with Gain 81.20.Keywords: Analytical chemistry; e-modules; Gravimetri; Inquiry based learning; Volumetry